2019
DOI: 10.4236/as.2019.1010094
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Phenolic Compounds from Olive Leaf Extracts and Their Effect on Proliferation of Human Carcinoma Cell Lines

Abstract: The aim of this work was to evaluate the effect of different olive leaf extracts (OLE) from different leaf growing stages on human carcinoma cell lines. OLE were tested in human carcinoma cell lines in vitro and cells were plated in 96-microtiter culture plates for each OLE concentration. Fresh (F) and freeze-dried (FD) leaves exhibited phenolic compounds in the range of 2.09 ± 0.10 to 8.44 ± 0.64 and 7.72 ± 0.56 to 24.65 ± 1.9 mg gallic acid equivalents/g leaves, respectively. OLE from several Portuguese oliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The lowest TPC found in fresh leaf samples (26.56 ± 1.59 mg/g GAE) when compared with dried leaves. Similar observations have been reported in previous studies on dried M. oleifera leaves compared to fresh leaves ( Zullaikah et al, 2019 , Saini et al, 2014 ) and in several types of leaves ( Martinho et al, 2019 , Roshanak et al, 2016 , Rabeta and Lin, 2015 ). It is also worth noting that Hossain et al (2010) even reported that the lower total phenolics and antioxidant capacity of fresh samples were not due to the dilution effect caused by its high moisture content, even after they corrected for its moisture content values.…”
Section: Discussionsupporting
confidence: 91%
“…The lowest TPC found in fresh leaf samples (26.56 ± 1.59 mg/g GAE) when compared with dried leaves. Similar observations have been reported in previous studies on dried M. oleifera leaves compared to fresh leaves ( Zullaikah et al, 2019 , Saini et al, 2014 ) and in several types of leaves ( Martinho et al, 2019 , Roshanak et al, 2016 , Rabeta and Lin, 2015 ). It is also worth noting that Hossain et al (2010) even reported that the lower total phenolics and antioxidant capacity of fresh samples were not due to the dilution effect caused by its high moisture content, even after they corrected for its moisture content values.…”
Section: Discussionsupporting
confidence: 91%
“…The phenolic and flavonoid content of olive leaves varies according to many factors such as climatic conditions, moisture content, age and variety of the plant, agricultural practices and the extraction procedures used (Ghomari et al, 2019). Martinho et al (2019) found that phenolic compounds in fresh and freeze-dried leaves ranging from 2.09 to 8.44 and 7.72 to 24.65 mg gallic acid equivalents/g leaves, respectively. Furthermore, the free radical scavenging activities of extracts was measured by the ability to scavenge DPPH radical.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, extracts from mango leaves or from other parts of this plant are capable of exerting a protective effect against different types of breast cancer, through its cytotoxic and anti-proliferative effect, which cannot be associated with a single component of the extract, but to the synergistic effect of the different polyphenols present [30,41]. Furthermore, grape pomace and olive leaf extracts seem to inhibit the proliferation of colon cancer cells [42] and different human carcinoma cell lines [43], respectively.…”
Section: Discussionmentioning
confidence: 99%